Preparation method of artemisinin slow-release functional implant

CN122874648APending Publication Date: 2026-10-09THE NAVAL MEDICAL UNIV OF PLA
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611178878.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-05
Publication Date
2026-10-09

AI Technical Summary

Technical Problem

[0006]目前尚未见公开将青蒿素直接用于牙种植体表面涂层,构建兼具抗炎与促成骨功能的种植体系统的技术方案

Benefits of technology

[0040]本发明提供的青蒿素缓释功能种植体的制备方法,围绕青蒿素类药物的特点,在同一涂层系统中同时引入抗炎、抗氧化和骨整合促进三种作用的组分。在种植体植入早期,青蒿素的持续释放有望减轻手术区域的炎症反应,降低炎性细胞因子水平和氧化应激强度,从而为骨愈合创造更加稳定的环境;中后期较低浓度的药物可以在不抑制成骨细胞活性的前提下发挥一定的调节作用,促进骨形成与骨结合。与传统抗生素和高浓度金属离子涂层相比,青蒿素类药物耐药风险较低,毒性相对温和,更适合作为长期植入装置的局部功能因子。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122874648A_ABST
    Figure CN122874648A_ABST
Patent Text Reader

Abstract

The application discloses a preparation method of an artemisinin slow-release functional implant, and belongs to the technical field of medical implants.The preparation method comprises the following steps: immersing the prepared implant with a transition bonding layer into an obtained uniform suspension system, standing, and obtaining an implant with an artemisinin composite coating; sterilizing the implant with the artemisinin composite coating, and packaging in a sterile environment to obtain the artemisinin slow-release functional implant.The artemisinin slow-release functional implant is designed by taking artemisinin drugs as a core controlled-release coating, and a new technical approach is provided for preventing inflammation around the implant and optimizing bone integration from the material level without changing the overall morphology of the implant, so that the artemisinin slow-release functional implant has good clinical transformation potential.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of pharmaceutical preparation technology, specifically, it relates to a method for preparing an artemisinin sustained-release functional implant. Background Technology

[0002] Dental implants have become an important means of tooth restoration, but the incidence of peri-implantitis is increasing year by year, and it is one of the main causes of implant failure and implant loss. Its characteristics include inflammation of the peri-implant mucosa and continuous alveolar bone resorption, often related to the adhesion of various bacterial biofilms to the implant surface. Current prevention and treatment methods include mechanical debridement, ultrasonic / air-blasting polishing, laser or chemical disinfection (such as chlorhexidine, hydrogen peroxide), supplemented by systemic or local antibiotics, but these often have limited effectiveness against mature biofilms and are difficult to stop the progression of bone resorption.

[0003] Therefore, in recent years, numerous studies have attempted to construct functional coatings on implant surfaces, including: antibacterial coatings: such as antibiotic (doxycycline, minocycline, vancomycin), antimicrobial peptides, and metal nanoparticle (Ag, Cu, ZnO, etc.) loaded coatings, aiming to inhibit early bacterial adhesion and biofilm formation. Osteogenesis / immunomodulatory coatings: introducing bone morphogenetic protein (BMP-2), neurotrophic factors, Zn / Cu-doped hydroxyapatite, biomimetic nanofibers, etc., onto the implant surface to improve osseointegration and regulate the surrounding immune microenvironment.

[0004] The above demonstrates that achieving local sustained release through drug / bioactive molecule coatings is feasible, and appropriate surface structures (roughness, micro / nano structures) and biomolecules can promote osteointegration and soft tissue closure. However, the following limitations exist: antibiotic / metal ion antibacterial coatings are prone to drug resistance, cytotoxicity, or long-term safety issues; osteogenic factors (such as BMP-2) are expensive, have poor stability, narrow dosage windows, and excessive dosage can easily induce ectopic osteogenic or inflammation; most coating designs separate antibacterial and osteogenic functions, failing to achieve the synergistic effect of "antibacterial inhibition + inflammation regulation + bone regeneration promotion".

[0005] Existing studies have shown that artemisinin and its derivatives have significant anti-inflammatory, antioxidant, and osteogenic effects in the bone / periodontal field. For example, artemisinin loaded onto cerium-doped mesoporous calcium silicate nanomaterials can promote the proliferation of human periodontal ligament fibroblasts and improve the blood compatibility of biomaterials. In addition, several reviews of traditional Chinese medicine combined with bone regeneration indicate that artemisinin-derived terpene lactones are expected to enhance bone formation and bone repair capacity by regulating oxidative stress and immune responses.

[0006] Currently, there is no publicly available technical solution for directly applying artemisinin to the surface coating of dental implants to construct an implant system that combines anti-inflammatory and bone-promoting functions. Summary of the Invention

[0007] The purpose of this invention is to provide a method for preparing artemisinin-sustaining implants.

[0008] To achieve the above objectives, the technical solution adopted by the present invention is as follows:

[0009] In a first aspect, the present invention provides a method for preparing an artemisinin-sustaining implant, comprising the following steps:

[0010] The first step is to immerse the pretreated implants in a solution until the solution completely submerges the pretreated implants, thereby obtaining implants with a transitional bonding layer.

[0011] The solution is selected from dopamine solution, calcium phosphate solution, simulated body fluid SBF solution, and sol-gel solution;

[0012] The second step, the preparation method of artemisinin-loaded functional particles, includes the following steps:

[0013] Mesoporous particles and artemisinin-like compounds with a mass ratio of 1 to 10:1 (preferably 5:1) were dissolved in anhydrous ethanol and magnetically stirred at room temperature for 12 to 36 h (preferably 24 h). After the reaction was completed, the mixture was centrifuged (5000 rpm, 5 min) and dried (at a temperature of 50°C for 12 h) to obtain functional particles loaded with artemisinin.

[0014] The artemisinin compounds are selected from artemisinin, dihydroartemisinin, and artesunate;

[0015] The mesoporous particles are selected from calcium silicate particles with mesoporous structures and mesoporous bioglass (m-BG) particles.

[0016] The third step, the method for preparing implants with artemisinin composite coatings, includes the following steps:

[0017] Artemisinin-loaded functional particles are dispersed in a biodegradable polymer solution to obtain a uniform suspension system with a concentration of 10-40 mg / mL (preferably 25 mg / mL).

[0018] The prepared implant with a transitional bonding layer is immersed in the obtained uniform suspension system and left to stand (preferably for 10 min) to obtain an implant with an artemisinin composite coating;

[0019] Alternatively, the prepared implant with a transitional bonding layer can be sprayed with a uniform suspension system to obtain an implant with an artemisinin composite coating.

[0020] Alternatively, the prepared implant with a transitional bonding layer can be spin-coated into a uniform suspension system to obtain an implant with an artemisinin composite coating;

[0021] The biodegradable polymer is selected from PLGA (polylactic acid-glycolic acid copolymer), PCL (polycaprolactone), gelatin, polylactic acid (PLA), polyhydroxybutyrate (PHB), hyaluronic acid, and alginic acid;

[0022] The fourth step involves sterilizing the implants with artemisinin composite coating prepared in the fourth step (using low-temperature sterilization methods (ethylene oxide or low-temperature plasma); or low-dose gamma sterilization), and then encapsulating them in a sterile environment to obtain artemisinin sustained-release implants.

[0023] Preparation of the dopamine solution: Dopamine hydrochloride is added to a 5-15 mmol / L (preferably 10 mmol / L) Tris-HCl buffer solution at pH 8.5 and stirred at room temperature until completely dissolved to obtain a dopamine solution with a concentration of 1-3 mg / mL (preferably 2 mg / mL).

[0024] Preparation of the sol-gel solution: Tetraethoxysilane (TEOS) at a volume ratio of 1:3 is mixed with anhydrous ethanol. Under continuous stirring, 0.01~0.1 mol / L (preferably 0.05 mol / L) hydrochloric acid solution is slowly added dropwise to make the molar ratio of water to TEOS 6:1. Stirring is continued at room temperature (25℃) (preferably for 45 min), and the mixture is allowed to stand for 12~24 h (preferably 18 h) to obtain the sol-gel solution.

[0025] When the solution is a dopamine solution, calcium phosphate solution, or sol-gel solution, it needs to be treated as follows: let it stand at room temperature (20~25℃) for 6~18 hours (preferably 12 hours). After the reaction is completed, take out the sample and rinse it with deionized water at least 3 times (3~6 min each time, preferably 5 min), sonicate or gently shake it, blow it dry with nitrogen or dry it under vacuum at a temperature of 40~60℃ for 30~60 min.

[0026] When the solution is a simulated body fluid SBF solution, it needs to be treated as follows: shaken at 37°C for 48 hours, with fresh SBF solution replaced every 24 hours, then ultrasonically cleaned with deionized water and dried with nitrogen.

[0027] Preparation of the pretreated implant:

[0028] The metal implant is sequentially ultrasonically cleaned with acetone and then ultrasonically cleaned with anhydrous ethanol, dried, and then subjected to sandblasting and acid etching to form a micro-nano rough surface. It is then removed and ultrasonically cleaned with deionized water until the pH of the washing solution is close to neutral. It is then neutralized with 0.05~0.15 M (preferably 0.1 M) sodium bicarbonate solution (preferably for 60 s), washed with deionized water, and dried (dried with nitrogen and at 60°C for 60 minutes) to obtain the pretreated implant.

[0029] The metal implant is made of titanium alloy, medical-grade pure titanium, or zirconium-containing titanium alloy.

[0030] The sandblasting uses alumina (Al2O3) particles with a particle size range of 500 μm; the sandblasting pressure is 2.5 bar (approximately 36 psi); the nozzle and distance are as follows: the nozzle diameter is 2 mm, and the distance between the sandblasting nozzle and the sample surface is 20 cm; the spray angle is approximately 90° (nearly vertical); the sandblasting time / coverage is 30 s per location; immediately after sandblasting, ultrasonic cleaning is performed to remove residual sand particles: ultrasonic cleaning is performed for 15 minutes in deionized water or anhydrous ethanol, followed by ultrasonic cleaning in deionized water for another 10 minutes; drying is performed by blowing with nitrogen.

[0031] The acid etching treatment uses a mixed acid, which is made by mixing concentrated sulfuric acid (H2SO4, 98%) and concentrated hydrochloric acid (HCl, 38%) in a volume ratio of 1:1.

[0032] The acid etching process involves immersing the sandblasted and pre-cleaned sample in a mixed acid preheated to 60-70°C for 60 minutes, while maintaining gentle stirring or shaking during the process.

[0033] Preparation of the mesoporous calcium silicate particles: Tetraethoxysilane (TEOS) and anhydrous ethanol are mixed in a volume ratio of 1:1 to 5 (preferably 1:3). A calcium nitrate tetrahydrate solution with a volume ratio of 1:1 is mixed with the above solution, and the concentration of the calcium nitrate tetrahydrate solution is 0.05 to 0.5 g / mL (preferably 0.12 g / mL). Then, hexadecyltrimethylammonium bromide is added, and the mass ratio of hexadecyltrimethylammonium bromide to calcium nitrate tetrahydrate is 1:1 to 5 (preferably 1:2.4). Ammonia is added to adjust the pH of the system. Up to step 10-11, the mixture is stirred at a temperature of 40-60℃ (preferably 50℃) for 12-36 hours (preferably 24 hours), then hydrothermally treated at a temperature of 110-130℃ (preferably 120℃) under sealed conditions for 12-36 hours (preferably 24 hours). After cooling, the mixture is centrifuged and washed at least 3 times, then dried at a temperature of 60-80℃ (preferably 70℃) for 12-36 hours (preferably 24 hours). The resulting solid is calcined at a temperature of 500-600℃ (preferably 550℃) for 4-6 hours (preferably 5 hours) to obtain calcium silicate particles with a mesoporous structure.

[0034] The preparation method of the mesoporous bioglass (m-BG) particles is as follows: At room temperature, tetraethyl orthosilicate (TEOS), triethyl phosphate (TEP), calcium nitrate tetrahydrate, and hydrochloric acid solution with a concentration of 0.1-1 mol / L (preferably 0.5 mol / L) are sequentially added to an anhydrous ethanol solution of polyethylene oxide-polypropylene oxide-polyethylene oxide triblock copolymer (P123) with a concentration of 0.01-0.1 g / mL (preferably 0.067 g / mL). The mixture is stirred for 12-36 h (preferably 24 h) to obtain a homogeneous precursor sol. The obtained precursor sol is allowed to stand at room temperature to allow the solvent to slowly evaporate, and evaporation induces self-assembly to form a gel. After the solvent has completely evaporated, the obtained gel is collected and dried to constant weight. The dried gel is ground into powder and heated to 700 °C at a heating rate of 1 °C / min. The product is calcined at ℃ for 4-6 hours (preferably 5 hours), then naturally cooled to room temperature. The resulting product is then ground and sieved to obtain mesoporous bioglass (m-BG) particles.

[0035] Preparation of the biodegradable polymer solution: The biodegradable polymer is added in batches to ethyl acetate and stirred (preferably for 45 min), then filtered (using a 0.45 μm PTFE filter) to obtain a biodegradable polymer solution with a concentration of 10~30 mg / mL (20 mg / mL).

[0036] The spraying conditions are as follows: pneumatic spray gun or micro-mist spray gun, nozzle diameter 0.2~0.5 mm, spraying pressure 0.1~0.3 MPa, spraying distance (from nozzle to sample) 10~20 cm, and liquid consumption of 0.5 mL per spray based on coverage.

[0037] The spin coating conditions are as follows: suspension system volume: 1.0 mL; rotation speed (rpm): 2000 rpm, 30~60 s.

[0038] The spin coating can be layered: repeating the spin coating 1 to 5 times can achieve the target thickness (curing at 40°C for 10 to 30 minutes between each layer).

[0039] By adopting the above technical solution, the present invention has the following advantages and beneficial effects:

[0040] The method for preparing artemisinin-suppressed functional implants provided by this invention, based on the characteristics of artemisinin-based drugs, simultaneously introduces components with three effects—anti-inflammatory, antioxidant, and bone integration-promoting—into the same coating system. In the early stages of implantation, the sustained release of artemisinin is expected to reduce the inflammatory response in the surgical area, decrease the levels of inflammatory cytokines and the intensity of oxidative stress, thereby creating a more stable environment for bone healing. In the mid-to-late stages, lower concentrations of the drug can exert a certain regulatory effect without inhibiting osteoblast activity, promoting bone formation and osseointegration. Compared with traditional antibiotics and high-concentration metal ion coatings, artemisinin-based drugs have a lower risk of drug resistance and relatively mild toxicity, making them more suitable as local functional factors for long-term implantation devices.

[0041] This invention immobilizes artemisinin in a composite coating of mesoporous inorganic particles and a polymer. By adjusting process parameters such as particle pore structure, polymer type, and coating thickness, different release curves can be obtained, thus matching patients with different healing rates and inflammation levels according to clinical needs. Simultaneously, the transitional bonding layer design improves the adhesion between the coating and the metal substrate, making the coating less prone to peeling under implantation and chewing forces, which is beneficial for maintaining long-term function. The preparation process provided by this invention is compatible with existing titanium implant surface treatment processes. The required equipment and raw materials are relatively common, and it has the basis for engineering scale-up. It can not only be applied to newly produced implants but also to surface modification of some existing implant models, expanding the existing product line.

[0042] In summary, this invention, through a controlled-release coating design centered on artemisinin-based drugs, provides a new technical approach for peri-implant inflammation prevention and osseointegration optimization at the material level without altering the overall morphology of the implant, and has good potential for clinical translation. Attached Figure Description

[0043] Figure 1This is a schematic diagram showing the increase in coating quality of artemisinin-releasing implants.

[0044] Figure 2 This is a schematic diagram of the in vitro cumulative release curve of artemisinin-controlled implants.

[0045] Figure 3 This is a schematic diagram of the coating adhesion strength test results.

[0046] Figure 4 This is a schematic diagram of the cell compatibility (CCK-8) results of artemisinin sustained-release implant extract.

[0047] Figure 5 This is a schematic diagram showing the results of artemisinin-releasing implant extract upregulating the expression of RUNX2, a key osteogenic factor.

[0048] Figure 6 This is a schematic diagram showing the effect of artemisinin-slow-release implant extract promoting the formation of mineralized nodules.

[0049] Figure 7 This is a schematic diagram showing the effect of artemisinin sustained-release implant extract in reducing the expression of the inflammatory factor IL-6.

[0050] Figure 8 This is a schematic diagram showing the inhibitory effect of artemisinin sustained-release implant extract on bacterial growth. Detailed Implementation

[0051] To more clearly illustrate the present invention, the following description, in conjunction with preferred embodiments, further clarifies the invention. Those skilled in the art should understand that the specific descriptions below are illustrative rather than restrictive, and should not be construed as limiting the scope of protection of the present invention.

[0052] This invention explicitly uses artemisinin and its derivatives (such as dihydroartemisinin, artesunate, artemether, etc.) as the main active ingredient in the functional coating on the implant surface. Through localized sustained release, it exerts anti-inflammatory, antioxidant, and bone metabolism-regulating effects around the implant, replacing traditional antibiotics or high-concentration metal ion antibacterial coatings. Artemisinin-based drugs play a dominant role in the coating, rather than being a minor auxiliary component, and are the core technological foundation for achieving the overall biological effect of this invention.

[0053] This invention employs a layered surface structure design of "roughened metal substrate—transitional bonding layer—artemisinin controlled-release coating". On the substrate surface after conventional sandblasting and acid etching, a transitional bonding layer (such as a dopamine self-polymerizing layer, calcium phosphate layer, or mesoporous bioglass thin layer) is first constructed, and then an artemisinin-containing functional coating is formed on top of it. This layered structure ensures the original suitable roughness and osteointegration performance of the metal substrate, while significantly improving the bonding strength between the functional coating and the metal substrate through the transition layer, reducing the risk of coating peeling during implantation and under stress. Simultaneously, the transition layer itself has a certain degree of osteoconductivity, which can synergize with the biological effects of artemisinin.

[0054] This invention employs a composite coating of "mesoporous inorganic carrier + biodegradable polymer" to achieve controlled sustained release of artemisinin. The invention loads artemisinin-like drugs onto inorganic particles with mesoporous structures (such as mesoporous calcium silicate, mesoporous bioglass, and nano-hydroxyapatite), and then combines this with biodegradable polymers (such as PLGA, PCL, and gelatin) to form a functional surface coating. The mesoporous carrier provides a high specific surface area and adjustable pore size for controlling drug loading and diffusion channels; the biodegradable polymer regulates the penetration of bodily fluids and the degradation rate of the coating. Therefore, by adjusting the carrier pore size, polymer type, and coating thickness, the release rate and release time window of artemisinin-like drugs can be designed and controlled.

[0055] This invention focuses on a multi-functional approach combining anti-inflammatory, antioxidant, and osteogenic effects. It integrates the multi-target biological characteristics of artemisinin-based drugs with the structure of an implant surface coating. The goal is not merely to achieve a single antibacterial or osteogenic effect, but rather to design a multi-functional approach addressing the biological needs at different postoperative stages. In the early stages of implantation, it continuously releases artemisinin-based drugs to reduce local inflammation and oxidative stress. In the mid-to-late stages, it provides a favorable microenvironment for osteoblast adhesion, proliferation, and mineralization at lower concentrations, thus simultaneously preventing peri-implantitis and improving osseointegration quality. This holistic functional approach of "achieving multiple microenvironmental regulation with a single small-molecule drug" is a significant innovation that distinguishes it from existing antibiotic coatings or single growth factor coatings.

[0056] This invention relates to a surface modification and preparation route compatible with existing dental implant processing technologies: The preparation method of this invention involves subsequent surface modification based on conventional roughening processes such as sandblasting and acid etching for existing titanium implants. It only requires adding steps such as constructing a transitional bonding layer, preparing and coating the artemisinin loading carrier, outer layer conditioning treatment, and sterilization packaging. It does not require alteration to the macroscopic structure of the implant, nor does it rely on extreme high temperatures or complex equipment, exhibiting excellent process compatibility and industrial-scale potential. This ensures that this invention not only remains at the laboratory material design level but also has the feasibility of being directly implemented in existing production lines.

[0057] Example 1

[0058] Preparation method of artemisinin sustained-release functional implants

[0059] Step 1, Pre-treatment of metal implants:

[0060] Analytical purity acetone, anhydrous ethanol (≥99.5%), and deionized water ≥18 MΩ·cm

[0061] The titanium alloy implant was ultrasonically cleaned in acetone for 10 minutes at a moderate power (bath water temperature not exceeding 30℃ to avoid excessive solvent evaporation). After removal, it was ultrasonically cleaned in anhydrous ethanol for 10 minutes, again controlling the bath water temperature to ≤30℃. Then, it was ultrasonically cleaned in deionized water for 10-15 minutes (can be divided into 2 × 5 minute cycles) to remove solvent residue and soluble impurities. Immediately after removal, the surface was dried with dust-free nitrogen gas (filtered at 0.2 μm) until no obvious watermarks remained. Quality control inspection: No visible oil stains or fingerprints were observed; a quick assessment could be made using contact angle measurement or surface resistance / optical methods (an excessively high contact angle may indicate residual organic contamination).

[0062] The implants were sequentially treated with sandblasting and acid etching to form a micro-nano rough surface. After removal, they were immediately rinsed with a large amount of deionized water and ultrasonically cleaned three times in deionized water for 10 minutes each time until the pH of the washing solution was close to neutral (pH 7). The solution was then neutralized with 0.1 M NaHCO3 (sodium bicarbonate) solution (60 s) and rinsed with deionized water to avoid residual carbonate. The implants were then dried (blown with nitrogen and placed in a 60℃ drying oven for 60 minutes) to obtain the pretreated implants.

[0063] The blasting uses alumina (Al2O3) particles with a particle size range of 500 μm; the blasting pressure is 2.5 bar (approximately 36 psi); nozzle and distance: nozzle diameter is 2 mm, distance between the blasting nozzle and the sample surface is 20 cm; the blasting angle is approximately 90° (nearly vertical). Blasting time / coverage: 30 s / position per area, the overall blasting time is adjusted according to the implant size and texture until the target roughness (Ra) or a visible uniform roughening effect is achieved. Generally, multiple short sweeps are used instead of long concentrated bombardment to avoid local over-cutting. Immediately after blasting, ultrasonic cleaning is performed to remove residual abrasive particles: ultrasonic cleaning for 15 minutes in deionized water or anhydrous ethanol, followed by another 10 minutes of ultrasonic cleaning in deionized water. Drying: nitrogen drying. Surface roughness Ra is measured (target based on design, common dental SLA target Ra≈3 μm); surface morphology is observed using SEM to confirm the absence of obvious particle embedding or surface melt marks. If alumina is used, it is necessary to confirm whether the amount of residual particles after sandblasting is within an acceptable range (e.g., by testing the Al content using EDS).

[0064] The acid etching treatment uses a mixed acid, which is made by mixing concentrated sulfuric acid (H2SO4, 98%) and concentrated hydrochloric acid (HCl, 38%) in a volume ratio of 1:1.

[0065] The acid etching process involves immersing the sandblasted and pre-cleaned sample in a mixed acid preheated to 60-70°C for 60 minutes, while maintaining gentle stirring or shaking during the process.

[0066] The second step is to construct the transition bonding layer:

[0067] Preparation of dopamine solution: Weigh 0.020 g of dopamine hydrochloride and add it to 10 mL of 10 mmol / L Tris-HCl buffer solution at pH 8.5. Stir magnetically at room temperature until completely dissolved to prepare a 2 mg / mL dopamine solution. Prepare and use immediately.

[0068] The pretreated implants obtained in the first step were immersed in a dopamine solution, ensuring complete immersion, and allowed to react at room temperature (20-25°C) for 12 hours. After the reaction, the samples were removed and rinsed three times with deionized water for 5 minutes each time, followed by ultrasonic or gentle shaking to remove unreacted residues. The implants were then dried under nitrogen or in a clean, vacuum oven at 40-60°C for 30-60 minutes to obtain implants with a transitional bonding layer rich in catechol structures.

[0069] The third step, the preparation method of artemisinin-loaded functional particles, includes the following steps:

[0070] Preparation of calcium silicate particles with mesoporous structure: Tetraethoxysilane (TEOS) and anhydrous ethanol were mixed at a volume ratio of 1:3. 2.36 g of calcium nitrate tetrahydrate was dissolved in 20 mL of deionized water to form a transparent solution. The solution was added to 20 mL of the above solution, and then hexadecyltrimethylammonium bromide (CTAB, 1 g) was added. Ammonia water was added to adjust the pH of the system to 10-11. The mixture was stirred at 50 °C for 24 h, transferred to a closed reactor, and hydrothermally treated at 120 °C for 24 h. After cooling, the mixture was centrifuged and washed three times, and dried at 70 °C for 24 h. The resulting solid was calcined at 550 °C for 5 h to remove the template agent, thus obtaining calcium silicate particles with mesoporous structure.

[0071] Calcium silicate particles with a mesoporous structure (1.0 g, 5 mmol), artemisinin (0.20 g), and 20 mL of anhydrous ethanol were mixed and magnetically stirred at room temperature for 24 h to promote the entry of drug molecules into the mesoporous structure and adsorption on the inner surface. After the reaction was completed, the excess solvent was removed by centrifugation (5000 rpm, 5 min). The resulting solid was dried at 50 °C for 12 h to obtain functional particles loaded with artemisinin.

[0072] The fourth step, the method for preparing implants with artemisinin composite coatings, includes the following steps:

[0073] The 0.50 g artemisinin-loaded functional particles obtained in the third step were dispersed in 20 mL of a biodegradable polymer solution with a concentration of 20 mg / mL to obtain a uniform suspension system.

[0074] Preparation of biodegradable polymer solution: 0.4 g PLGA was added in portions to 20 mL ethyl acetate and stirred on a magnetic stirrer for 45 min. The mixture was then filtered (using a 0.45 μm PTFE filter) to obtain a biodegradable polymer solution with a concentration of 20 mg / mL.

[0075] The implant with the transitional bonding layer prepared in the second step was immersed in 20 mL of the obtained homogeneous suspension system and left to stand for 10 min to obtain an implant with an artemisinin composite coating.

[0076] Step 5: Sterilization and Packaging

[0077] The implants with artemisinin composite coating prepared in step four are sterilized (by low-temperature sterilization methods (ethylene oxide or low-temperature plasma); or by low-dose gamma sterilization), and then encapsulated in a sterile environment to obtain artemisinin sustained-release implants.

[0078] Example 2

[0079] Replace step 4 in Example 1 with the following content, and keep the other steps the same as in Example 1.

[0080] The implant with the transitional bonding layer prepared in the second step is sprayed with a uniform suspension system to obtain an implant with an artemisinin composite coating.

[0081] Spraying conditions: pneumatic spray gun or micro-mist spray gun, nozzle diameter 0.2~0.5 mm, spraying pressure: 0.1~0.3 MPa, spraying distance (from nozzle to sample): 10~20 cm, liquid consumption per spraying is 0.5 mL based on coverage.

[0082] Example 3

[0083] Replace step 4 in Example 1 with the following content, and keep the other steps the same as in Example 1.

[0084] The implant with the transitional bonding layer prepared in the second step is spin-coated into a uniform suspension system to obtain an implant with an artemisinin composite coating.

[0085] Spin coating conditions: Suspension system volume: 1.0 mL; Spin coating speed (rpm): 2000 rpm, 30~60 s.

[0086] Multilayer coating: Repeat spin coating 1 to 5 times to obtain the target thickness (cure each layer by drying at 40°C for 10 to 30 minutes).

[0087] Example 4

[0088] Replace the second step of constructing the transition bonding layer in Example 1 with the following content, and the other steps are the same as in Example 1.

[0089] The pretreated implants obtained in the first step were immersed in a calcium phosphate solution, and the method and steps were the same as in Example 1, to obtain implants with a transitional bonding layer; the bonding layer is a thin layer of calcium phosphate.

[0090] Alternatively, the pretreated implants obtained in the first step can be immersed in simulated body fluid (SBF) solution and shaken at 37°C for 48 hours, with the SBF solution replaced with fresh solution every 24 hours. Then, the implants are ultrasonically cleaned with deionized water and dried with nitrogen to obtain implants with a transitional bonding layer.

[0091] Example 5

[0092] Replace the second step of constructing the transition bonding layer in Example 1 with the following content, and the other steps are the same as in Example 1.

[0093] The pretreated implant obtained in the first step was immersed in a sol-gel solution, and the method and steps were the same as in Example 1, to obtain an implant with a transitional bonding layer; the bonding layer is a thin layer of silicon-containing bioactive glass.

[0094] Preparation of sol-gel solution: Tetraethoxysilane (TEOS) and anhydrous ethanol were mixed at a volume ratio of 1:3. Under continuous stirring, 2.8 mL of 0.05 mol / L hydrochloric acid solution was slowly added dropwise to make the molar ratio of water to TEOS approximately 6:1. The mixture was stirred for 45 min at room temperature (25℃) and allowed to stand for 18 h to mature, thus obtaining the sol-gel solution.

[0095] Example 6

[0096] Replace step 3 in Example 1 with the following content, and keep the other steps the same as in Example 1.

[0097] Calcium silicate particles with a mesoporous structure (1.0 g, 5 mmol), dihydroartemisinin (0.20 g, 0.70 mmol), and 20 mL of anhydrous ethanol were mixed and magnetically stirred at room temperature for 24 h to promote the entry of drug molecules into the mesoporous structure and adsorption on the inner surface. After the reaction was completed, the excess solvent was removed by centrifugation (5000 rpm, 5 min). The resulting solid was dried at 50 °C for 12 h to obtain functional particles loaded with artemisinin.

[0098] Example 7

[0099] Replace step 3 in Example 1 with the following content, and keep the other steps the same as in Example 1.

[0100] Calcium silicate particles with a mesoporous structure (1.0 g, 5 mmol), artesunate (0.20 g, 0.52 mmol), and 20 mL of anhydrous ethanol were mixed and magnetically stirred at room temperature for 24 h to promote drug molecules to enter the mesoporous structure and adsorb onto the inner surface. After the reaction was completed, excess solvent was removed by centrifugation (5000 rpm, 5 min). The resulting solid was dried at 50 °C for 12 h to obtain functional particles loaded with artemisinin.

[0101] Example 8

[0102] Replace step 3 in Example 1 with the following content, and keep the other steps the same as in Example 1.

[0103] Mesoporous bioglass (m-BG) particles (1 g), artesunate (0.20 g, 0.52 mmol), and 20 mL of anhydrous ethanol were mixed and magnetically stirred at room temperature for 24 h to promote drug molecules to enter the mesoporous structure and adsorb onto the inner surface. After the reaction was completed, the supernatant was discarded by centrifugation (5000 rpm, 5 min), and the solid precipitate was collected. The obtained solid was dried at 50 °C for 12 h to obtain functional particles loaded with artemisinin.

[0104] Preparation method of mesoporous bioglass (m-BG) particles: 2.0 g of template agent, polyethylene oxide-polypropylene oxide-polyethylene oxide triblock copolymer (P123), was added to 30 mL of anhydrous ethanol and magnetically stirred at room temperature until completely dissolved. Then, 3.6 mL of tetraethyl orthosilicate (TEOS), 0.34 mL of triethyl phosphate (TEP), 0.70 g of calcium nitrate tetrahydrate, and 1.0 g of 0.5 mol / L hydrochloric acid solution were added sequentially, and magnetic stirring was continued for 24 h to obtain a homogeneous precursor sol. The obtained precursor sol was transferred to a petri dish and allowed to stand at room temperature to allow the solvent to slowly evaporate, inducing self-assembly into a gel. After complete solvent evaporation, the resulting gel was collected and dried in a drying oven to constant weight. The dried gel was ground into powder and placed in a muffle furnace, heated to 700 °C at a rate of 1 °C / min, and calcined for 5 h to remove the template agent and residual organic matter, forming a mesoporous structure. After calcination, the mixture was allowed to cool naturally to room temperature, and the resulting product was ground and sieved to obtain mesoporous bioglass (m-BG) particles.

[0105] Example 9

[0106] I. Structural and Morphological Characterization

[0107] 1. Quantitative estimation of coating quality increment and film thickness

[0108] To verify the consistency of the coating quality and the controllability of the coating thickness of the artemisinin sustained-release functional implants prepared according to the present invention, six implants prepared in the same batch according to the method of Example 1 were weighed before and after coating, and the coating mass increment Δm was calculated. The coating thickness h was estimated using a mass-volume conversion method, combining the implant surface area A and the coating density ρ. The test results are shown in Table 1. To more intuitively illustrate the differences between samples, the Δm of each sample was plotted as a bar chart, as shown in Figure 1.

[0109] Table 1. Estimate of mass increment and thickness of artemisinin sustained-release implant coating.

[0110]

[0111] The data in the table show that the coating mass increment Δm of the six implants in the same batch was within the range of 1.64~1.83 mg, with an average of approximately 1.72±0.07 mg (n=6), indicating that the coating quality was controllable and the consistency within the batch was good. Based on the surface area A and coating density ρ, the coating thickness h was 5.86~6.54 μm, with an average of approximately 6.16±0.24 μm, indicating that the thin-layer coating prepared by this invention has a stable thickness and is suitable for subsequent drug sustained release. Figure 1 This is a schematic diagram showing the quality improvement of the coating on the artemisinin-releasing implant. The diagram demonstrates that the coating quality is uniform and the process is controllable.

[0112] 2. Specific Surface Area and Pore Size (BET) Analysis

[0113] To verify the loading capacity of the carrier particles for artemisinin and its effect on pore structure, nitrogen adsorption-desorption tests were conducted on mesoporous calcium silicate particles and mesoporous bioglass (m-BG) particles before and after artemisinin loading. The specific surface area was calculated using the BET method, and the pore volume and pore size distribution were analyzed using the BJH method. The test results are shown in Table 2.

[0114] Table 2. BET specific surface area and pore structure parameters of mesoporous carrier particles before and after loading artemisinin.

[0115]

[0116] The data in the table show that the specific surface area and pore volume of both types of mesoporous carriers decreased by about 15-20% after loading artemisinin, while the average pore size remained in the range of 3.5-4.5 nm. This indicates that the drug molecules mainly enter the mesoporous channels and partially occupy the pore volume without destroying the overall pore structure of the carrier, which is consistent with the purpose of sustained drug release in this invention.

[0117] 3. FTIR / XRD / XPS Analysis

[0118] To verify the loading state of artemisinin on the carrier particles of the present invention and its interaction with the carrier, Fourier transform infrared spectroscopy (FTIR), X-ray diffraction (XRD) and X-ray photoelectron spectroscopy (XPS) analyses were performed on the blank carrier particles and the particles loaded with artemisinin, respectively.

[0119] In FTIR tests, both mesoporous calcium silicate particles (blank support) and mesoporous bioglass particles (blank support) exhibited typical characteristic absorption peaks such as Si-O-Si and Si-O-Ca. After loading artemisinin, the sample showed characteristic absorption peaks of the drug, such as COC and CH, and the positions and relative intensities of the characteristic absorption peaks of the original silica groups on the support did not change significantly, suggesting that artemisinin was loaded onto the particle surface and inside the pores in a physical adsorption form without disrupting the support's skeletal structure.

[0120] XRD tests showed that mesoporous calcium silicate particles (blank carrier) and mesoporous bioglass particles (blank carrier) exhibited amorphous diffuse peaks or broad peaks. No new impurity phase peaks or phase transition signals were observed after loading artemisinin. The original peak shape and position of the carrier remained consistent, indicating that the drug loading process did not induce crystal form changes or structural rearrangements.

[0121] XPS analysis further revealed that after loading artemisinin, the sample showed weak peaks in the C 1s and O 1s regions corresponding to some functional groups of the drug. At the same time, the binding energy peaks of matrix elements such as Si and Ca did not shift, indicating that the interaction between the drug and the carrier was mainly physical rather than chemical, and that the elemental composition and energy level state of the carrier surface were not changed.

[0122] Table 3 Comparison of characteristic peaks / crystal forms before and after artemisinin loading onto the carrier

[0123]

[0124] II. Validation of Drug Loading and In Vitro Sustained-Release Performance

[0125] 1. Drug loading and encapsulation efficiency

[0126] To verify that the artemisinin-loaded functional particles prepared in the third step of this invention possess effective drug loading capacity, the drug loading and encapsulation efficiency (EE) of the artemisinin-loaded functional particles were measured. The measurements were performed using ultraviolet-visible spectroscopy (UV-Vis), and the specific results are shown in Table 4.

[0127] Table 4. Drug loading and encapsulation efficiency of artemisinin-loaded functional particles

[0128]

[0129] The data in the table show that the drug loading of the artemisinin-loaded functional particles prepared in the third step of this invention is about 5.7% (w / w), and the encapsulation efficiency is about 79.5%. The differences between the three samples are small, indicating that the process of this invention can achieve stable and repeatable drug loading.

[0130] 2. In vitro release test: cumulative release curve (most standard)

[0131] To evaluate the in vitro drug release behavior of the artemisinin sustained-release functional implants prepared in Example 1 of this invention, the artemisinin sustained-release functional implants were placed in phosphate-buffered saline (PBS, pH 7.4) containing 0.5% (v / v) Tween-80 and cultured at 37 °C with shaking. Samples were taken at preset time points (1, 3, 7, and 14 days) to determine the artemisinin concentration in the supernatant, and the supernatant was replenished with an equal volume of fresh drug release medium. Drug concentration was determined using UV-Vis spectrophotometry or high-performance liquid chromatography. The cumulative release at each time point was calculated based on the standard curve and converted to a cumulative release percentage (% cumulative release). Typical test results are shown in Table 5, and the corresponding cumulative release curves are shown in Figure 2.

[0132] Table 5. Cumulative in vitro release percentage of artemisinin-controlled release implants

[0133]

[0134] Figure 2 This is a schematic diagram of the in vitro cumulative release curve of the artemisinin sustained-release functional implant. As can be seen from the figure, the artemisinin sustained-release functional implant prepared in Example 1 of this invention releases only about 25% of the drug in the first 24 hours, and exhibits a continuous and gradual cumulative release process over 14 days. The cumulative release amount at 14 days is about 80-85%, indicating that the coating system can effectively suppress explosive release and achieve medium- to long-term sustained release.

[0135] The artemisinin-sustaining implants prepared by the method of this invention were placed in PBS (pH 7.4, containing 0.5% Tween-80) and cultured with shaking at 37 °C. The artemisinin content in the supernatant was measured at different time points, and the cumulative release percentage was calculated. The curves showed that the cumulative release was approximately 25% in the first day, followed by a slow and continuous increase over 3–14 days, reaching approximately 80–85% cumulative release at day 14. This indicates that the coating of this invention has a significant sustained-release effect and avoids excessive initial burst release.

[0136] III. Verification of Coating Adhesion, Tolerance and Stability

[0137] 1. Ultrasonic stability test

[0138] To evaluate the tolerability of the artemisinin sustained-release functional implant prepared in Example 1 of this invention during routine clinical pretreatment, the artemisinin sustained-release functional implant prepared in Example 1 of this invention was placed in deionized water and immersed in an ultrasonic cleaner (frequency 40 kHz, power 100 W) for continuous ultrasonic cleaning at room temperature for 10 min, which was considered as one cycle. After each cycle, the implant was removed, gently blown dry or air-dried, weighed and recorded. This was repeated for 3 cycles, and the coating mass loss rate was calculated. The test results are shown in Table 6.

[0139] Table 6. Results of Ultrasonic Stability Tests on Artemisinin-Release Functional Implants

[0140]

[0141] The data in the table show that after three 10-minute ultrasonic cycles, the coating mass loss rate of each sample was less than 0.2%, and no obvious flaking or visible defects were observed. This indicates that the coating on the artemisinin sustained-release functional implant prepared in this invention has good adhesion stability and mechanical tolerance under conventional ultrasonic cleaning conditions, which can meet the requirements for coating integrity during clinical pretreatment and daily cleaning.

[0142] 2. Residual solvent detection (GC)

[0143] To evaluate the residual organic solvent content in the artemisinin sustained-release functional implants prepared in Example 1 of this invention, the coating material cut off from the finished implants or the coating material completely peeled off was used to ultrasonically extract the residual solvent from the coating material with an appropriate amount of solvent (such as methanol). The supernatant was then used for gas chromatography (GC) detection. Ethanol and ethyl acetate were quantified using the external standard method, and calibration curves were established. The limits of detection (LOD) were all below 5 ppm. Three implants from the same batch were selected for testing, and the results are expressed as residual solvent content (ppm, i.e., μg / g), as shown in Table 7.

[0144] Table 7 Residual solvent content in artemisinin-controlled release implants

[0145]

[0146] As can be seen from the data in the table, the residual amounts of ethanol and ethyl acetate in the coating prepared and dried by the process of this invention are both in the tens of ppm range, and the total amount of residual solvent is less than 50 ppm, which is far below the general limit requirements for residual organic solvents in pharmaceutical preparations. This indicates that the coating prepared by this invention has virtually no organic solvent residue after drying, and provides good safety assurance for clinical applications.

[0147] 3. Coating adhesion test

[0148] To evaluate the bonding strength between the coating and the implant substrate, a pull-out test was used to determine the coating adhesion strength. The specific method was as follows: a standard pull-out post (5 mm in diameter) was glued to the coating surface, cured with adhesive, and then placed in a pull-out testing machine. It was pulled vertically at a constant loading speed until the coating peeled off or the interface failed. The maximum tensile force was recorded and the adhesion strength σadh (MPa) was calculated. Three artemisinin-releasing implants prepared in Example 1 of this invention from the same batch were selected for testing, and the results are as follows: Figure 3 As shown, Figure 3 This is a schematic diagram of the coating adhesion strength test results. As can be seen from the diagram, the pull-out test shows that the coating adhesion strength is approximately 1.2 MPa, with little difference between samples.

[0149] IV. Biological Functional Verification

[0150] 1. Cell compatibility (CCK-8)

[0151] To evaluate the cell compatibility of the artemisinin sustained-release functional implants prepared in Example 1 of this invention, a coating implant extract was prepared according to the relevant ISO 10993 standard. Cells were seeded in 96-well plates and cultured for 1, 3, 5, 7, 10, and 14 days with the extract added. Cell viability was detected at each time point using the CCK-8 assay, and the relative cell viability was calculated with the absorbance of the blank control group (cells + complete culture medium) at the same time point as 100%. The corresponding curves are shown in Figure 4. Figure 4 This is a schematic diagram of the cell compatibility (CCK-8) results of the artemisinin sustained-release implant extract. As shown in the figure, CCK-8 assays were performed on cells exposed to the coated implant extract for 1, 3, 5, 7, 10, and 14 days, with relative viability calculated using the blank control group as the baseline at 100% cell viability. The results show that the relative cell viability was close to 100% at 1 day, then decreased slightly with prolonged culture time, but remained at approximately 90% at 14 days, without a sharp decline or significant inhibition. This indicates that the coated extract of this invention has no significant cytotoxicity to cells and exhibits good long-term cell compatibility.

[0152] 2. Osteogenesis promoting effect

[0153] To evaluate the promoting effect of the artemisinin sustained-release functional implant prepared in Example 1 of this invention on osteogenic differentiation of stem cells, the expression of the key osteogenic transcription factor RUNX2 protein and the formation of late-stage mineralized nodules were detected. First, Western blot analysis was used to analyze the effect of the coated implant extract on the early stage of osteogenic differentiation. The results showed that compared with the ordinary implant extract group, the RUNX2 expression in the coated implant extract group of this invention was significantly enhanced (…). Figure 5 Subsequently, Alizarin Red S staining was used to evaluate the formation of mineralized nodules in the late stage of osteogenic differentiation. The results showed that after 14 days and 21 days of culture, the deposition of mineralized nodules in the artemisinin sustained-release functional implant extract group prepared in Example 1 of this invention was significantly increased, and the staining was deeper, indicating a significant enhancement in the degree of mineralization. Figure 6 The above results indicate that the artemisinin sustained-release functional implant prepared in Example 1 of this invention can promote osteogenic differentiation of stem cells and enhance mineralization capacity, which is beneficial to the integration of the implant with the surrounding bone tissue.

[0154] Figure 5 This is a schematic diagram showing the upregulation of RUNX2, a key osteogenic factor, by the artemisinin-release implant extract. Western blot analysis showed that, compared with the conventional implant extract group (Con), the RUNX2 protein expression was enhanced in the coated implant extract group (ART) of this invention, suggesting that it can promote early osteogenic differentiation of stem cells.

[0155] Figure 6This is a schematic diagram showing the results of artemisinin-releasing implant extract promoting the formation of mineralized nodules. Alizarin Red S staining shows that at 14 and 21 days of culture, compared with the ordinary implant extract group (Con), the artemisinin-releasing implant extract group (ART) prepared in Example 1 of this invention showed significantly enhanced mineralized nodule deposition and deeper staining, suggesting that this invention can promote the mineralization process in the later stage of osteogenic differentiation.

[0156] In summary, the artemisinin sustained-release functional implant prepared in this invention not only has good cell compatibility, but also promotes RUNX2 expression in the early stage of osteogenic differentiation and enhances the formation of mineralized nodules in the later stage of osteogenic differentiation, indicating that it helps to improve the bone integration efficiency and early stability of the implant.

[0157] 3. Anti-inflammatory effect

[0158] To evaluate the anti-inflammatory effect of the artemisinin-sustaining implant prepared in Example 1 of this invention, Western blot was used to detect the protein expression level of the key inflammatory factor IL-6. Cells were cultured in both ordinary implant extract and the artemisinin-sustaining implant extract prepared in Example 1 of this invention. Proteins were extracted and IL-6 expression was detected under inflammatory stimulation conditions. The results showed that compared with the ordinary implant extract group, the artemisinin-sustaining implant extract prepared in Example 1 of this invention significantly reduced the expression level of IL-6, suggesting that it has a good anti-inflammatory effect. Figure 7 ).

[0159] Figure 7 This is a schematic diagram showing the results of the artemisinin-releasing implant extract reducing the expression of the inflammatory factor IL-6. Western blot analysis showed that, under inflammatory stimulation conditions, the IL-6 expression in the artemisinin-releasing implant extract group (ART) prepared in Example 1 of this invention was significantly weaker than that in the ordinary implant extract group (Con), indicating that this invention has the effect of inhibiting the production of inflammatory factors and is beneficial to improving the inflammatory microenvironment around the implant.

[0160] The inflammatory microenvironment is a key factor affecting osseointegration and long-term stability of implants. Elevated levels of pro-inflammatory factors such as IL-6 can inhibit osteogenic differentiation and promote bone resorption. This invention improves the inflammatory environment by reducing IL-6 levels, which helps to increase the clinical success rate of implants.

[0161] 4. Antibacterial activity

[0162] To evaluate the antibacterial activity of the artemisinin-sustaining implant prepared in Example 1 of this invention, the plate colony counting (CFU) method was used to detect the effects of ordinary implant extract (Con) and the coating extract (ART) of this invention on bacterial growth. Both extracts were added to the bacterial suspension and cultured for 24 h before dilution, coating, and colony counting. The results are as follows: Figure 8 As shown, the colony-forming units in the ART group were significantly lower than those in the Con group, approximately 1 log 10 The reduction in bacterial load indicates that the artemisinin sustained-release coating of this invention can effectively inhibit bacterial proliferation. This antibacterial effect helps reduce the bacterial load around the implant, reduce inflammatory response, and provide a favorable microenvironment for subsequent osteogenic and osseointegration.

[0163] Figure 8 This is a schematic diagram showing the inhibitory effect of artemisinin-controlled-release implant extract on bacterial growth. The plate count method was used to evaluate the inhibitory effects of conventional implant extract (Con) and artemisinin-controlled-release implant extract (ART) on bacterial growth. The results showed that the ART group had a higher colony-forming unit (log) count. 10 The CFU / mL level was significantly lower than that of the Con group, approximately 1 log [value missing]. 10 The decrease in the amount indicates that the coating prepared in this invention has significant antibacterial activity.

[0164] The artemisinin sustained-release implant prepared by this invention has both antibacterial and anti-inflammatory functions, which can jointly improve the soft and hard tissue environment around the implant, and improve the long-term stability and clinical success rate of the implant.

[0165] The artemisinin sustained-release implant prepared by this invention is used to improve early osseointegration efficiency after implantation: The artemisinin sustained-release implant prepared by this invention can continuously release the drug after implantation, thereby shortening the osseointegration time and improving the quality of osseointegration by inhibiting the inflammatory response, enhancing antioxidant capacity, promoting osteoblast differentiation and mineralization, and improving the bone microenvironment around the implant.

[0166] The artemisinin sustained-release implant prepared in this invention is used to reduce the level of inflammation in the early stage of implantation and improve healing: Artemisinin has the effect of inhibiting inflammatory pathways such as NF-κB and NLRP3, which can reduce the level of inflammatory factors such as IL-6 and TNF-α in the local area after surgery, reduce postoperative reactive inflammation, and help stabilize the healing of soft tissue and bone tissue around the implant.

[0167] The artemisinin sustained-release functional implant prepared in this invention is used to inhibit common oral pathogens and early biofilm adhesion: artemisinin and its analogues have inhibitory effects on a variety of Gram-positive / negative bacteria, including Streptococcus mutans, Porphyromonas gingivalis, etc., which helps to reduce the risk of early implant infection or biofilm formation and prevent early peri-implantitis.

[0168] The artemisinin sustained-release implant prepared by this invention is used to improve the implant healing environment for patients with bone defects or poor bone quality: For patients with poor bone mass, bone density or bone blood supply (such as smokers, mild diabetes, mild osteoporosis, etc., the surgeon shall handle them accordingly), this invention can improve local bone regeneration capacity and improve implant stability by continuously providing drugs with osteogenic enhancement effects.

[0169] The artemisinin sustained-release functional implant prepared by this invention is used to improve the success rate of implants in environments with high microbial load or high risk of inflammation: in cases with a history of periodontitis, poor oral hygiene, or easy accumulation of food around defective restorations, the sustained-release artemisinin coating can enhance the implant's dual protection of "anti-inflammatory + antibacterial".

[0170] The above description is merely a preferred embodiment of the present invention and is not intended to limit the present invention in any way. Although the present invention has been disclosed above with reference to preferred embodiments, it is not intended to limit the present invention. Any person skilled in the art can make some modifications or alterations to the above-described technical content to create equivalent embodiments without departing from the scope of the present invention. Any simple modifications, equivalent changes, and alterations made to the above embodiments based on the technical essence of the present invention without departing from the scope of the present invention shall still fall within the scope of the present invention.

Claims

1. A method for preparing an artemisinin-sustaining implant, characterized in that, Includes the following steps: The first step is to immerse the pretreated implants in a solution until the solution completely submerges the pretreated implants, thereby obtaining implants with a transitional bonding layer. The solution is selected from dopamine solution, calcium phosphate solution, simulated body fluid SBF solution, and sol-gel solution; The second step, the preparation method of artemisinin-loaded functional particles, includes the following steps: Mesoporous particles and artemisinin-like compounds with a mass ratio of 1 to 10:1 were dissolved in anhydrous ethanol and magnetically stirred at room temperature for 12 to 36 h. After the reaction was completed, the mixture was centrifuged and dried to obtain functional particles loaded with artemisinin. The artemisinin compounds are selected from artemisinin, dihydroartemisinin, and artesunate; The mesoporous particles are selected from calcium silicate particles with mesoporous structures and mesoporous bioglass particles. The third step, the method for preparing implants with artemisinin composite coatings, includes the following steps: Artemisinin-loaded functional particles were dispersed in a biodegradable polymer solution to obtain a uniform suspension system with a concentration of 10-40 mg / mL. The prepared implant with a transitional bonding layer was immersed in the obtained uniform suspension system and left to stand to obtain an implant with an artemisinin composite coating. Alternatively, the prepared implant with a transitional bonding layer can be sprayed with a uniform suspension system to obtain an implant with an artemisinin composite coating. Alternatively, the prepared implant with a transitional bonding layer can be spin-coated into a uniform suspension system to obtain an implant with an artemisinin composite coating; The biodegradable polymer is selected from PLGA, PCL, gelatin, polylactic acid, polyhydroxybutyrate, hyaluronic acid, and alginate; The fourth step involves sterilizing the implant with the artemisinin composite coating prepared in the fourth step, and then encapsulating it under sterile conditions to obtain an artemisinin sustained-release implant.

2. The method for preparing artemisinin-sustaining functional implants according to claim 1, characterized in that, Preparation of the dopamine solution: Add dopamine hydrochloride to a 5-15 mmol / L Tris-HCl buffer solution at pH 8.5 and stir at room temperature until completely dissolved to obtain a dopamine solution with a concentration of 1-3 mg / mL.

3. The method for preparing artemisinin-sustaining functional implants according to claim 1, characterized in that, Preparation of the sol-gel solution: Tetraethoxysilane (TEOS) at a volume ratio of 1:3 was mixed with anhydrous ethanol. Under continuous stirring, 0.01-0.1 mol / L hydrochloric acid solution was slowly added dropwise to make the molar ratio of water to TEOS 6:

1. Stirring was continued at room temperature, and the mixture was allowed to stand for 12-24 hours to mature, thereby obtaining the sol-gel solution.

4. The method for preparing artemisinin-sustaining functional implants according to claim 1, characterized in that, When the solution is a dopamine solution, calcium phosphate solution, or sol-gel solution, it needs to be treated as follows: let it stand at room temperature for 6 to 18 hours. After the reaction is complete, take out the sample, rinse it with deionized water at least 3 times, sonicate or gently shake it, blow it dry with nitrogen or dry it under vacuum at a temperature of 40 to 60°C for 30 to 60 minutes.

5. The method for preparing artemisinin-sustaining functional implants according to claim 1, characterized in that, When the solution is a simulated body fluid SBF solution, it needs to be treated as follows: shaken at 37°C for 48 hours, with fresh SBF solution replaced every 24 hours, then ultrasonically cleaned with deionized water and dried with nitrogen.

6. The method for preparing artemisinin-sustaining functional implants according to claim 1, characterized in that, Preparation of the pretreated implant: The metal implants were sequentially ultrasonically cleaned with acetone and then with anhydrous ethanol, dried, and then subjected to sandblasting and acid etching to form a micro-nano rough surface. They were then removed and ultrasonically cleaned with deionized water until the pH of the washing solution was close to neutral. The solution was then neutralized with 0.05~0.15M sodium bicarbonate solution, rinsed with deionized water, and dried to obtain the pretreated implants.

7. The method for preparing artemisinin-sustaining functional implants according to claim 6, characterized in that, The metal implant is made of titanium alloy, medical-grade pure titanium, or zirconium-containing titanium alloy.

8. The method for preparing artemisinin-sustaining functional implants according to claim 1, characterized in that, Preparation of the biodegradable polymer solution: The biodegradable polymer is added to ethyl acetate in batches and stirred, then filtered to obtain a biodegradable polymer solution with a concentration of 10~30 mg / mL.

9. The method for preparing artemisinin-sustaining functional implants according to claim 1, characterized in that, The spraying conditions are as follows: pneumatic spray gun or micro-mist spray gun, nozzle diameter 0.2~0.5 mm, spraying pressure 0.1~0.3 MPa, spraying distance 10~20 cm, and liquid consumption of 0.5 mL per spray based on coverage.

10. The method for preparing artemisinin-sustaining functional implants according to claim 1, characterized in that, The spin coating conditions are as follows: suspension system volume: 1.0 mL; rotation speed: 2000 rpm, 30~60 s.